Anti-nociceptive activity of Pereskia bleo Kunth. (Cactaceae) leaves extracts - Ikarastika Rahayu Abdul Wahab; Carolina Carvalho Guilhon; Patricia Dias Fernandes; Fabio Boylan (Elsevier, 2012)
Ethnopharmacological relevance: Local communities in Malaysia consume Pereskia bleo Kunth.